Key Measurement and Feasibility Characteristics When Selecting Outcome Measures - Harrold, Megan; Elliott, D.; Berney, S.; Skinner, E. (2015)
Selection of appropriate outcome measures to assess progress in physical rehabilitation across the complete recovery continuum is essential but may pose challenges in clinical practice. This paper examines key measurement and feasibility characteristics for outcome measures, using critical care survivors as an exemplar. With increased survivorship following a critical illness, initiatives to improve the recovery trajectory for patients have become a focus for clinicians and researchers. For this patient cohort, we present a 3-tier framework and use of standing and non-standing patient phenotypes to guide instrument selection. Key measurement issues for clinicians to consider include the responsiveness, criterion validity, and reliability of functional assessment instruments. Patient-centered factors that may influence performance and the effectiveness of assessments include frailty, fatigue, and other varied symptoms of patient discomfort. Suggestions to address these challenges are discussed, specifically prioritizing outcome measurement according to tier, consideration of patient and ICU-related factors, and recommendations to standardize outcome measurement to a core set.